A Combined Ultrafiltration/Diafiltration Step Facilitates the Purification of Cyanovirin-N From Transgenic Tobacco Extracts - Opdensteinen, Patrick; Clodt, Juliana I.; Müschen, Catherine R.; Filiz, Volkan; Buyel, Johannes F. (Frontiers in Bioengineering and Biotechnology, 2019)
The production of biopharmaceutical proteins in plants offers many advantages over traditional expression platforms, including improved safety, greater scalability and lower upstream production costs. However, most products are retained within plant cells instead of being secreted, so downstream processing necessarily involves cell disruption followed by the removal of abundant particles and host cell proteins (HCPs). We investigated whether ultrafiltration/diafiltration (UF/DF) can simplify the purification of the model recombinant protein cyanovirin-N (CVN), an ~11 kDa HIV-neutralizing lectin, from tobacco extracts prior to chromatography. We compared different membrane types and process conditions, and found that at pH 8.0 and 50 mS cm-1 an UF step using a 100 kDa regenerated cellulose membrane removed more than 80% of the ~0.75 mg mL-1 total soluble protein present in the clarified plant extract. We recovered ~70% of the CVN and the product purity increased ~3 fold in the permeate. The underlying effects of tobacco HCP retention during the UF/DF step were investigated by measuring the zeta potential and particle size distribution in the 2–10,000 nm range. Combined with a subsequent 10 kDa DF step, this approach simultaneously reduced the process volume, conditioned the process intermediate, and facilitated early, chromatography-free purification. Due to the generic, size-based nature of the method, it is likely to be compatible with most products smaller than ~50 kDa.